The C# implementation of numerical calculation process on non linear equation solutions - Yahya Yahya; Amri Muliawan Nur (Jurnal Informatika, 2018)
Solutions in the process of resolving numerical methods, especially "Solutions of Non Linear Equations", are determined by several criteria including: 1. Solutions will be obtained if the tolerances found from numerical calculations are less than or equal to the specified tolerances, depending on the criteria of the question. 2. The solution will be obtained if the function value f(xn +1) reaches zero (0). 3. The solution will be obtained if the value of xn+1 has a constant value (no change). In some observations of manual efforts to find non-linear equations solutions, students cannot do the calculation perfectly. This is due to lack of understanding of teaching materials or modules and also the algorithms that are difficult to grasp. Moreover, the calculation has to be done for several times iterations in order to obtain the expected results. Comparing the results of calculations done manually using Microsoft Excel and the result of calculations using numerical applications created using C# programming language, it concludes: non-linear equations manual calculation to get one of the roots of non-linear functions tend to not completed in a short time so the error rate and accuracy cannot be measured. The calculations performed using Microsoft Excel, obtained the error rate reaches 0.158% and the accuracy rate reaches 99.842%. Calculations performed using numerical applications using the C# programming language obtained error rate reached 0.004% and accuracy rate reached 99.996%.